Epidemiology of Emergent Madariaga Encephalitis in a Region with Endemic Venezuelan Equine Encephalitis: Initial Host Studies and Human Cross-Sectional Study in Darien, Panama. - Amy Y Vittor; Blas Armien; Publio Gonzalez; Jean-Paul Carrera; Claudia Dominguez; Anayansi Valderrama; Greg E Glass; Davis Beltran; Julio Cisneros; Eryu Wang; Alex Castillo; Brechla Moreno; et al. (PLoS Neglected Tropical Diseases, 2016)
Neurotropic arboviral infections are an important cause of encephalitis. A zoonotic, vector-borne alphavirus, Madariaga virus (MADV; formerly known as South American eastern equine encephalitis virus), caused its first documented human outbreak in 2010 in Darien, Panama, where the genetically similar Venezuelan equine encephalitis virus (VEEV) is endemic. We report the results of a seroprevalence survey of animals and humans, illustrating contrasting features of MADV and VEEV ecology and epidemiology.Small mammals were trapped in 42 sites in Darien, Panama, using Sherman traps, Tomahawk traps, and mist nets for bats. Blood was tested for the presence of neutralizing antibodies to MADV and VEEV. In addition, bird sera collected in 2007 in Chagres, Panama, were tested for MADV and VEEV neutralizing antibodies. Viremia was ascertained by RT-PCR. Human exposure to these two viruses was determined by IgG ELISA, followed by plaque reduction neutralization tests. To identify relevant risk factors for MADV or VEEV exposure, logistic regression analysis was performed, and the most parsimonious model was selected based on the Akaike information criterion.The animal survey yielded 32 bats (16 species), 556 rodents (12 species), and 20 opossums (4 species). The short-tailed cane mouse (Zygodontomys brevicauda) found abundantly in pasture and farms, had the highest MADV seroprevalence (8.3%). For VEEV, the shrub and forest-dwelling long-whiskered rice rat (Transandinomys bolivaris) had the highest seroprevalence (19.0%). Viremia was detected in one animal (Z. brevicauda). Of the 159 bird sera (50 species) tested, none were positive for either virus. In humans (n = 770), neutralizing antibodies to MADV and VEEV were present in 4.8% and 31.5%, respectively. MADV seropositivity was positively associated with cattle ranching, farming, and fishing. Having VEEV antibodies and shrubs near the house diminished risk. Age, forest work, farming and fishing were risk factors for VEEV, while having MADV antibodies, glazed windows, waste pick-up and piped water were protective.Our findings suggest that the short-tailed cane mouse and the long-whiskered rice rat serve as hosts for MADV and VEEV, respectively. The preferred habitat of these rodent species coincides with areas associated with human infection risk. Our findings also indicate that MADV emerged recently in humans, and that the transmission cycles of these two sympatric alphaviruses differ spatially and in host utilization.